Potential of cassava peels as a sustainable coagulant aid for institutional wastewater treatment: Characterisation, optimisation and techno-economic analysis - Kumar, V. (Elsevier B.V., 2021)
This work studies cassava peel starch (CPS) potential as a replacement for commercial chemical coagulants for treating institutional wastewater since the CPS is highly biodegradable with non-toxic sludge and relatively locally available and cheap to obtain. The treatment of wastewater by CPS was optimized using response surface methodology (RSM), while the applicability of CPS was estimated based on techno-economic analysis (TEA). The alum (control), CPS, and mixed (alum and CPS) coagulants were optimized in terms of pH, dosage and settling time as independent factors. The optimal turbidity, total suspended solids (TSS), and chemical oxygen demand (COD) removal were recorded at pH 9, with 30 mg/L and after 34.34 min for alum at which the removal rates were 83.44, 76.83 and 32.87, respectively (R2 = 0.83). At pH 6.0, with 448.58 mg/L of CPS and after 43.23 min, the removal rate was 60.19 for turbidity, 57.79 for TSS, and 30.19 for COD (R2 = 0.86). At pH 8, with 4:1 ratio (CPS: alum) and after 60 min, the removal efficiency was 77.48, 77.34 and 56.89, respectively (R2 = 0.82). CPS's efficiency is related to the presence of functional groups and elements, as determined by FTIR and XRF. The TEA shows that the CPS application is economically feasible, with a 34.49 internal return rate. The specific cost of pure CPS coagulant production is USD 1295.00 per ton, which is lower than the market cassava starch price of USD 3300.00 per ton. CPS provides an alternative method for chemical flocculation for wastewater treatment. Â© 2020 Elsevier B.V.